Efficacy of Daptomycin-Cloxacillin Combination in Experimental Foreign-Body Infection Due to Methicillin-Resistant Staphylococcus aureus - Garrigós, C. (American Society for Microbiology, 2012)
Despite the use of daptomycin alone at high doses (greater than 6 mg/kg of body weight/day) against difficult-to-treat infections, clinical failures and resistance appeared. Recently, the combination daptomycin-cloxacillin showed enhanced efficacy in clearing bacteremia caused by methicillin-resistant Staphylococcus aureus (MRSA). The aim of this study was to evaluate the efficacy of daptomycin at usual and high doses (equivalent to 6 and 10 mg/kg/day in humans, respectively) in combination with cloxacillin in a rat tissue cage infection model by MRSA and to compare its efficacy to that of daptomycin-rifampin. We used MRSA strain ATCC BAA-39. In the log- and stationary-phase kill curves, daptomycin-cloxacillin improved the bactericidal activity of daptomycin, especially in log phase. For in vivo studies, therapy was administered intraperitoneally for 7 days with daptomycin at 100 mg/kg/day and 45/mg/kg/day (daptomycin 100 and daptomycin 45), daptomycin 100-cloxacillin at 200 mg/kg/12 h, daptomycin 45-cloxacillin, and daptomycin 100-rifampin at 25 mg/kg/12 h. Daptomycin-rifampin was the best therapy (P < 0.05). Daptomycin 45 was the least effective treatment and did not protect against the emergence of resistant strains. There were no differences between the two dosages of daptomycin plus cloxacillin in any situation, and both protected against resistance. The overall effect of the addition of cloxacillin to daptomycin was a significantly greater cure rate (against adhered bacteria) than that for daptomycin alone. In conclusion, daptomycin-cloxacillin enhanced modestly the in vivo efficacy of daptomycin alone against foreign-body infection by MRSA and was less effective than daptomycin plus rifampin. The benefits of adding cloxacillin to daptomycin should be especially evaluated against infections by rifampin-resistant MRSA and for protection against the emergence of daptomycin nonsusceptibility.